Gus Baha's online preaching culture in Islam and media ethnography perspectives - Turhamun, Turhamun; Basit, Abdul; Riswan, Yulianingsih (IBDA` : Jurnal Kajian Islam dan Budaya, 2023)
Islam in media communication, examining its representation on platforms such as Instagram. The emergence of media ethnography, particularly in the context of digital media, and its relevance in studying diverse cultural artifacts, including Islamic content. The purpose of this study is to explain in general the principles and relationship between ethnographic media and Islamic cultural phenomena portrayed. As a research methodology, media ethnographic views all elements that are important in the digital world. Because communication can be interpreted with various symbols or symbols. Symbols can be in verbal and non-verbal forms, including Islamic ones. K.H. Ahmad Bahauddin Nursalim's ngaji online program is the case focused on in this study. The results first show that the principles of media ethnography in the online world can facilitate the interaction process. Second, in the context of virtual communication, media ethnography methods encourage the creation of effects on society, so that it can influence people’s culture and communication behavior in the virtual world. Third, Gus Baha, through his ngaji online, exemplifies the attitudes and behaviors of pesantren and Javanese culture, through the kitab kuning and Javanese language represented in his lectures. Fourth, the characteristics of his da'wah represent exactly the soul of Ki Ageng Suryomentaram.